How elite mountain climbers train to cope with hypoxia - Egan, S.; Burke, S. (13. International Hypoxia-Symposium, February, 19-22, 2003, Banff, Alberta (Kanada), 2003)
A group of elite climbers (n 5 39) were interviewed in order to assess their physical and mental training techniques prior to attempting to summit Mount Everest. Among the climbers were one of the first climbers to summit Everest without oxygen, the oldest climber to summit (64 years), the oldest climber to attempt to summit (71 years), the climber with the most summits and three female climbers. A qualitative method of inquiry (interview) was used to assess the mental techniques used by the climbers. A quantitative method (Questionnaire/interview) was used to collect data on the physical training. The main emphasis of the training was aerobic fitness and ability to regulate one`s breathing, ability to focus, ability to pray and finding inner peace. The physical modalities of training focused mostly on climbing (stairs, hills & mountains); running; cycling; hiking & cross country skiing. The mental training modalities were: meditation; yoga; breathing techniques; music and prayer. The study concluded that the three main factors that trigger mountain sickness in acclimatizing climbers are: The fear factor, inability to relax and inability to breathe correctly. All three are closely linked to one`s physical and mental fitness.